Multimodal-imaging characteristics of a prolapsed ureterocele causing an acute urethral obstruction in a dog - Yeunhea Lee; Hyoju Kim; Jaeeun Ko; Kidong Eom; Jaehwan Kim (Veterinární Medicína, 2020)
A 2-year-old Yorkshire Terrier was presented with haematuria and dysuria. On the ultrasonography, an irregularly shaped, cystic, intraluminal urinary bladder mass was identified at the left ureterovesical junction. The computed tomographic excretory urography and magnetic resonance imaging revealed a pouch-like cystic mass arising from the distal ureter embedded at the ureterovesical junction. The distal portion of the mass prolapsed into the proximal urethra and obstructed the urethral lumen. The multimodal imaging findings were consistent with a prolapsed ureterocele and were further confirmed with surgery and histopathology. After surgical removal of the mass, the clinical signs clearly improved. To the best of our knowledge, this is the first report of multimodal imaging characteristics and the outcome of a prolapsed ureterocele in a dog.